Deteksi Kesalahan Ejaan dan Penentuan Rekomendasi Koreksi Kata yang Tepat Pada Dokumen Jurnal JTIIK Menggunakan Dictionary Lookup dan Damerau-Levenshtein Distance - Tusty Nadia Maghfira; Imam Cholissodin; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Writing is a way to deliver and share information among people. It is now even easier to do because of the help of technology such as computers, smartphones and internet. For example, writing and publication of research journal is made to share and enhance knowledge. Generally, the publication of research journal is accommodated by educational institutions both national and international such as JTIIK (Jurnal Teknologi Informasi & Ilmu Komputer) Faculty of Computer Science UB. Before journal is published, a journal should pass editing process by editor to check if there is some mistake and deficiency such as spelling error. However, in their work, editor also accidentally making mistake that will lead to many error spelling that still exist even though editing process has been done. Some misspelled word can change the meaning of knowledge that the author want to deliver and cause misunderstanding of information among the readers. Based on these problems, researcher propose error spelling detection and correction system using Dictionary Lookup and Damerau-Levenshtein Distance. Dictionary Lookup method is considered effective in determining a word including validity or invalidity of the word based on availability or unavailability of the word in Lexical Resource. In addition, Damerau-Levenshtein Distance can provide better correction than Levenshtein Distance. The best precision and recall result for correction simultaneously are 0.78 and 1 from second test scenario.